Peran Perpustakaan dalam Meningkatkan Budaya Literasi Mahasiswa PAI di Universitas Ahmad Dahlan - Erchan, Nadya; Masduki, Yusron (Pustakaloka, 2023)
Abstract: The purpose of this research is to determine the role of the library in increasing the literacy culture of Islamic Religious Education students at Ahmad Dahlan University Yogyakarta, starting from an overview of the literacy culture of Islamic Religious Education students, then the efforts of the library in improving literacy culture as well as the inhibiting and supporting factors influencing the efforts of the library in improving the literacy culture of Islamic Religious Education students. Qualitative methods with a case study approach orCase Studies, The samples in this study were from campus 4 and campus 6 library staff as well as 8 Islamic Religious Education students of Jogja and Wates in 2019-2022. The results of the research shows that the role of the library in increasing the literacy culture is as a mediator and facilitator who provides programs and services so that it can support literacy cultural activities in the library but the cultural description of literacy of Islamic Religious Education students in 2022 is still classified as This can be proven through the intensity of visits by Islamic Religious Education students, namely only around 3-4 students out of a total of 932 Islamic Religious Education students from the 2019-2022 class and student interest in utilizing library services and programs in enhancing the literacy culture presented by the library has not done it optimally. The supporting factors are the procurement of relevant library materials and the inhibiting factors that exist in students, namely the lack of motivation and enthusiasm.Keywords : Library, Culture of Literacy, Islamic Religious Education Students Abstrak: Adapun tujuan dari penelitian ini yaitu untuk mengetahui peran perpustakaan dalam meningkatkan budaya literasi mahasiswa Pendidikan Agama Islam di Universitas Ahmad Dahlan Yogyakarta, mulai dari gambaran budaya literasi mahasiswa Pendidikan Agama Islam, kemudian upaya perpustakaan dalam meningkatkan budaya literasi serta faktor penghambat dan faktor pendukung yang mempengaruhi upaya perpustakaan dalam meningkatkan budaya literasi mahasiswa Pendidikan Agama Islam. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus atau Case Studies. Sampel dalam penelitian ini berasal dari staf perpustakaan kampus 4 dan kampus 6 serta 8 mahasiswa Pendidikan Agama Islam Jogja dan Wates Tahun 2019-2022. Hasil dari penelitian yang dilaksanakan menunjukkan bahwa peran perpustakaan dalam meningkatkan budaya literasi mahasiswa Pendidikan Agama Islam di Universitas Ahmad Dahlan Yogyakarta ialah sebagai mediator dan fasilitator yang menyediakan program dan layanan sehingga dapat mendukung kegiatan budaya literasi di perpustakaan namun gambaran budaya literasi mahasiswa Pendidikan Agama Islam pada tahun 2022 masih tergolong rendah hal ini dapat dibuktikan melalui intensitas kunjungan mahasiswa Pendidikan Agama Islam yaitu hanya berkisar 3-4 mahasiswa dari jumlah 932 mahasiswa Pendidikan Agama Islam Angkatan Tahun 2019-2022 dan minat mahasiswa dalam memanfaatkan layanan dan program perpustakaan dalam meningkatkan budaya literasi yang disajikan oleh pihak perpustakaan belum dilakukan secara maksimal. Adapun faktor pendukung berupa pengadaan bahan pustaka yang relevan serta faktor penghambat yang ada pada mahasiswa yaitu kurangnya motivasi dan semangat.Kata Kunci : Perpustakaan, Budaya Literasi, Mahasiswa PAI